EVALUASI PERBAIKAN INFILTRASI DAN PENURUNAN LIMPASAN PERMUKAAN MENGGUNAKAN BERBAGAI TEKNIK KONSERVASI TANAH PADA SISTEM AGROFORESTRI KOPI DI SUMBERMANJING WETAN - Dina Ananda Harfia; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2022)
The uneven distribution and intensity of rain cause a shortage and excess of water in dry land farming. It appears that the problem of soil conservation in principle is the regulation of the relationship between rainfall intensity, infiltration capacity, and runoff adjustment. To improve the physical properties of the soil, and the hydrological function of the land use it cannot only be stressed on the coffee plant. Other factors such as soil surface management, such as providing organic matter, covering the soil surface with understory plants, making absorption holes, terraces, waterways and so on, can improve the hydrological function of the land. Rainwater management can be carried out through controlling surface runoff, harvesting rainwater, increasing soil infiltration capacity, managing soil, controlling evaporation and seepage, lining waterways. The use of silt pit parallel is considered quite effective because it is able to produce the lowest surface runoff and sufficient water storage. Silt pit parallel can produce 0.6% of rainfall into surface runoff and also can store water as much as 62.35% of the rainfall that enters the plot. The functions of a silt pit are to increase water infiltration into the soil. On dry land, silt pit functions as a place for harvesting rainwater and surface runoff. Based on the correlation regression test, the amount of surface runoff is closely influenced by the intensity of rain or rainfall.